Type of bacterial isolates and antimicrobial resistance profile from different clinical samples at a Referral Hospital, Northwest Ethiopia: five years data analysis - Melkamu Abebe (BMC Research Notes, 2019)
Abstract Objective Antimicrobial resistance (AMR) is one of the most serious global public health threats that exert a significant burden in terms of patient morbidity and mortality and financial crises in many developing countries including Ethiopia. Knowledge on the type of predominantly circulating pathogens with their respective AMR profile in a given area is essential for optimal patient care. This study was aimed at assessing the types of bacterial isolates and their AMR profile identified from a range of clinical samples at Debre Markos Referral Hospital, Northwest Ethiopia, over a period of 5 years (2013 to 2017). Results From the total of 514 different clinical samples processed in the stated time frame, about 240 (46.7%) yield bacterial growth. Majority of the identified bacteria were isolated from stool culture 68 (28.3%) followed by urine 56 (23.3%), ear discharge 54 (22.5%) and wound swabs at 26 (10.8%). Most of the clinical isolates were Gram-negative at 171 (71.25%). The predominant isolate was S. aureus at 41 (17.1%) followed by Salmonella species, 40 (16.7%), Escherichia coli 36 (15%) and Pseudomonas aeruginosa at 26 (11.7%). Generally, the isolates were found resistant at (60–100%) against ampicillin, co-trimoxazole, doxycycline, gentamicin, norfloxacin and tetracycline. Gram-positive isolates were found relatively sensitive to ceftriaxone, erythromycin and vancomycin at (71–84%).